THE ROLE OF STOCKBROKERS IN THE DEVELOPMENT OF THE STOCK MARKET AND THE PROMOTION OF GLOBAL INVESTMENT - Zadvornykh, Serhii (Social Economics, 2025)
This study explores the evolving role of stockbrokers in the context of global financial market transformation and the rapid expansion of digital technologies. We examine how the traditional function of brokers as mere transaction intermediaries has shifted toward more complex roles, including analytical support, strategic advisory, and information intermediation, particularly in cross-border investment contexts. We analyze empirical data from diverse regulatory environments – including the United States, Canada, the European Union, Hong Kong, Japan, and South Africa – highlighting a global trend: while the number of brokerage firms is declining, the number of individual brokers is increasing, and so is the demand for analytical services. We argue that in regions where financial information is fragmented, regulatory frameworks are underdeveloped, or linguistic and cultural barriers impede investor decisions, brokers act as crucial facilitators of market transparency and information access. Our findings show that brokers, unlike financial analysts, are often better positioned to interpret local business conditions, communicate context-specific insights, and reduce informational asymmetries that discourage foreign capital inflows. This is especially significant for emerging and frontier markets. We further evaluate the challenges that brokers face as they assume analytical roles. These include the necessity of mastering digital tools, maintaining objectivity in financial reporting, and enhancing cybersecurity practices. Based on a mixed-methods approach that integrates content analysis, comparative market review, and basic statistical correlation, we have built a nuanced understanding of how the broker profession is adapting to fintech disruption and regulatory evolution. Our results suggest that brokers who successfully integrate traditional brokerage services with analytical competencies can enhance the quality of investment decisions, foster trust among international investors. We also analyzed the differences between the activities of classical financial analysts and stockbrokers engaged in analytical activities, as well as the gaps that the latter can fill, thereby improving the availability of necessary information for global investors.